Musik als Geschichte - Feil, Arnold (Muzikološki zbornik, 2007)
The article tries to clarify the dilemmas which arise when writing a history of music. The author raises the question abut the facts of music history and their interpretation, he tries to determine the object of history of music, introduces the important distinction between oral and notational music cultures and finaly examines the possibility of understanding the historical arch in light of idea of progress. Special problem represents the periodisation, which has next to the question what is music secondary value.
Keywords: ideja napredka; notacija; predmet glasbene zgodovine; ustno izročilo; zgodovina glasbe